Durasi Video Pembelajaran Dalam Flipped Classroom: Tinjauan Naratif Terhadap Dampaknya Pada Keterlibatan Dan Pemahaman Siswa - Hukom, Julham (CV. SINAR HOWUHOWU, 2025)
The purpose of this study was to explore the effect of video duration in the flipped classroom learning model on student engagement and understanding. The method used in this study was a narrative review, which reviewed and summarized various relevant studies published in the last five years regarding video duration and its impact on student learning experiences. The findings showed that the optimal video duration is highly dependent on the complexity of the material being delivered. Short videos are more effective for simple materials, while long videos are more appropriate for topics that require in-depth explanations, with the use of interactive elements such as questions and quizzes that increase student engagement. In addition, the technical quality of the video, including good visual and audio elements, greatly influences the effectiveness of learning. Based on these findings, practical recommendations for educators are to design learning videos that consider the appropriate duration for the topic being taught, as well as using interactive elements to maintain student engagement. In addition, it is important to ensure the quality of video production in order to support better understanding by students.